GP214 Increased marker of endothelial cell dysfunction sVCAM-1 in umbilical cord blood in neonates born to obese women. (June 2019) - novikova, valeria; Ivanov, Dmitriy; Petrenko, Yuriy; Yakovlev, Aleksey; Gurina, Olga; Varlamova, Olga; Blinov, Aleksey
Abstract : Introduction: Increased level of angiogenic and adhesion molecules released from adipose tissue in pregnant women with obesity may affect the process of angiogenesis, metabolic state and inflammatory potential in both mother and her offspring. Objectives: To determine the effect of maternal obesity on the level of sVCAM-1 and VEGF-A in mothers and their newborn babies. Methods: We conducted a prospective, observational study with the inclusion of 42 mothers and their newborn babies. Main group included 21 mothers with obesity and their newborn babies. Control group consisted of 22 women with normal body mass index (BMI) before and during pregnancies and their newborn babies. We analyzed serum concentrations of vascular cell adhesion molecule 1 (sVCAM-1) and vascular endothelial growth factor A (VEGF-A) in maternal cord blood and in venous blood of newborn babies in 2 day after birth. The normal level of sVCAM-1 for adults is 400.6-–1340.8 ng/ml; VEGF-A (for adults) - 0–42.6 pg/ml. Data was analyzed using the statistical package Statistica 10.0 for Windows-10. The significance of the differences was determined at P value < 0.05. Results: The level of markers of endothelial dysfunction in cord blood exceeded normal values in all examined women. Concentration of sVCAM-1 in maternal cord blood was significantly higher in women with obesity compare to women with normal BMI (4926.19±1158.63 ng/ml vs 3294.66±1338.23 ng/ml, p< 0, 0001). Concentration of VEGF-A in maternal cord blood in both groups (224.74±57.41pg/ml and 197.29±180.44 pg/ml; p>0.05), concentration of sVCAM-1 in newborns serum in both groups (4019.32±1024.45ng/ml and 4300.35±948.08 ng/ml, p>0.05) and concentration of VEGF-A in newborns serum in both groups (208.42±141.72pg/ml and 170.53±152.64 pg/ml; p>0.05) had no significant differences. The level of sVCAM-1 in cord blood was higher than in newborns serum in main group (4926.19 ±1158.63 and 4019.32±1024.45, p<0.05), but lower than in the control group (3294.66 ±1338.23 и 4300.35±948.08, p<0.05). We did not reveal any significant differences in level of VEGF-A in cord blood and in newborns serum in both groups. Conclusions: Pregnancy in obese women associated with chronic endothelial activation secondary to increased production of vascular cell adhesion molecule 1 (sVCAM-1). The level of markers of endothelial cell dysfunction in infants may be associated with a different course of the adaptation period. Pregestational or pregnancy associated disorders, can have a different impact on endothelial function in pregnant women. The dynamics of the endothelial dysfunction markers in umbilical cord blood and serum of infants requires additional study.